Organ Preservation in MSS Rectal Cancer - Gao, Yuye; Wu, Aiwen (Clinics in Colon and Rectal Surgery, 2023)
Rectal cancer is a heterogeneous disease with complex genetic and molecular subtypes. Emerging progress of neoadjuvant therapy has led to increased pathological and clinical complete response (cCR) rates for microsatellite stable (MSS) rectal cancer, which responds poorly to immune checkpoint inhibitor alone. As a result, organ preservation of MSS rectal cancer as an alternative to radical surgery has gradually become a feasible option. For patients with cCR or near-cCR after neoadjuvant treatment, organ preservation can be implemented safely with less morbidity. Patient selection can be done either before the neoadjuvant treatment for higher probability or after with careful assessment for a favorable outcome. Those patients who achieved a good clinical response are managed with nonoperative management, organ preservation surgery, or radiation therapy alone followed by strict surveillance. The oncological outcomes of patients with careful selection and organ preservation seem to be noninferior compared with those of radical surgery, with lower postoperative morbidity. However, more studies should be done to seek better regression of tumor and maximize the possibility of organ preservation in MSS rectal cancer.
Keywords: organ preservation; microsatellite stable; rectal cancer; watch-and-wait; local excision